Peran Literasi Keuangan dalam Meningkatkan Minat Investasi Saham pada Generasi Muda - Lidya Elfa; Richa Balqis; Rahma Thusuliha; M. Yusuf Bahtiar (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study examines the importance of financial literacy in encouraging young people's interest in stock investment. Low investment interest among young people is generally influenced by limited understanding of financial management and a lack of knowledge regarding capital markets. Therefore, financial literacy is seen as playing a crucial role in helping young people understand the benefits, risks, and how to invest appropriately. The study used a descriptive qualitative approach through data collection from various sources related to the investment behavior of young people. The results show that a good financial understanding can increase awareness, mindset, and interest in investing in stocks among young people. In addition to providing knowledge about fund management, financial literacy also helps individuals make more rational and targeted investment decisions. Therefore, improving financial literacy is a crucial step in building interest in stock investment among young people while supporting their ability to manage their finances more wisely and responsibly in the future.